Antibody Duration After Infection From SARS-CoV-2 in the Texas Coronavirus Antibody Response Survey. (6th May 2022) - Swartz, Michael D; DeSantis, Stacia M; Yaseen, Ashraf; Brito, Frances A; Valerio-Shewmaker, Melissa A; Messiah, Sarah E; Leon-Novelo, Luis G; Kohl, Harold W; Pinzon-Gomez, Cesar L; Hao, Tianyao; Zhang, Shiming; Talebi, Yashar; et al.
Abstract: Understanding the duration of antibodies to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus that causes COVID-19 is important to controlling the current pandemic. Participants from the Texas Coronavirus Antibody Response Survey (Texas CARES) with at least 1 nucleocapsid protein antibody test were selected for a longitudinal analysis of antibody duration. A linear mixed model was fit to data from participants (n = 4553) with 1 to 3 antibody tests over 11 months (1 October 2020 to 16 September 2021), and models fit showed that expected antibody response after COVID-19 infection robustly increases for 100 days postinfection, and predicts individuals may remain antibody positive from natural infection beyond 500 days depending on age, body mass index, smoking or vaping use, and disease severity (hospitalized or not; symptomatic or not). Abstract : A longitudinal model shows that expected antibody response after COVID-19 infection increases for 100 days postinfection, and predicts individuals may remain antibody positive beyond 500 days, depending on age, body mass index, smoking or vaping use, and disease severity.